**Simplify – square root of 49**

## Answer

-7

## Solution

**Negative square root of 49 = -√49**

Rewrite 49 as 7²

= – √7²

**Pull terms out from the radical, assuming positive real numbers.**

= -1 x 7

**Multiply -1 by 7**

= **-7**

Therefore, – square root of 49 is -7.

**Simplify – square root of 49**

-7

**Negative square root of 49 = -√49**

Rewrite 49 as 7²

= – √7²

**Pull terms out from the radical, assuming positive real numbers.**

= -1 x 7

**Multiply -1 by 7**

= **-7**

Therefore, – square root of 49 is -7.